Developing HERMS Temperature Control: A Study on PID-P and PI-P Cascade Control - Panaudomsup, Sumit; Subhagandha, Thanachok; Chanma, Kittidach; Boksuwan, Sungwan (My University, 2025)
The Heat Exchange Recirculating Mash System (HERMS) is widely utilized in craft brewing to maintain precise temperature control during the mashing process, which is critical for optimizing enzymatic activity and mash efficiency. This study explores the performance of two cascade control configurations: (1) a PID-P system, where an outer PID loop regulates an inner P loop, and (2) a PI-P system, where an outer PI loop regulates an inner P loop. The system was modeled using First-Order (FO) models, with control parameters optimized using Skogestad's tuning method. Simulations in MATLAB Simulink and real-world experimental validation were conducted to evaluate temperature stability, response time, energy efficiency, and wort quality. Results demonstrate that while both control strategies effectively maintain mash temperature, the PI-P configuration offers improved energy efficiency and reduced power fluctuations, making it more suitable for precision brewing applications. These findings contribute to optimizing HERMS temperature control, enhancing consistency, and reducing energy consumption in both home and industrial brewing setups.
Keywords: Cascade Control; Craft Brewing; HERMS; Mashing Process; Skogestad Tuning; Temperature Control